1995
DOI: 10.1038/jcbfm.1995.75
|View full text |Cite
|
Sign up to set email alerts
|

A Selective N-Type Calcium Channel Antagonist Reduces Extracellular Glutamate Release and Infarct Volume in Focal Cerebral Ischemia

Abstract: Although a number of studies have demonstrated the neuroprotective effects of antagonists of postsynaptic N-methyl-D-aspartate (NMDA) and non-NMDA receptors in cerebral ischemia, little is known about the treatment of cerebral infarction through presynaptic blocking of extracellular glutamate release. We evaluated the effects of a presynaptic selective N-type calcium channel antagonist (SNX-111, given intravenously by continuous infusion at 5 mg/kg/h from 20 min prior to occlusion until 2 h postocclusion) on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…On the other hand, a role of N-type Ca 2ϩ channels in pathophysiological processes of the brain ischemia has been reported using the rat permanent middle cerebral artery occlusion model, in which a peptide N-type Ca 2ϩ channel blocker w-conotoxin MVIIA decreased ischemia-induced glutamate releases. 5) Since cilnidipine has been shown to inhibit an elevation of intrathecal glutamate concentration in a pain model, 24) the Ntype Ca 2ϩ channel-blocking profile of cilnidipine may contribute its neuroprotective effect in the rat focal brain ischemia model. However, further extensive and careful examinations in vivo and in vitro should be planned since information, regarding the effects of cilnidipine on regional cerebral circulation, blood gases and brain temperature in animal models including the spontaneously hypertensive rats in addition to directly protective effects on damaging neuron, will be important to clarify mechanisms of its neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a role of N-type Ca 2ϩ channels in pathophysiological processes of the brain ischemia has been reported using the rat permanent middle cerebral artery occlusion model, in which a peptide N-type Ca 2ϩ channel blocker w-conotoxin MVIIA decreased ischemia-induced glutamate releases. 5) Since cilnidipine has been shown to inhibit an elevation of intrathecal glutamate concentration in a pain model, 24) the Ntype Ca 2ϩ channel-blocking profile of cilnidipine may contribute its neuroprotective effect in the rat focal brain ischemia model. However, further extensive and careful examinations in vivo and in vitro should be planned since information, regarding the effects of cilnidipine on regional cerebral circulation, blood gases and brain temperature in animal models including the spontaneously hypertensive rats in addition to directly protective effects on damaging neuron, will be important to clarify mechanisms of its neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Interestingly, several reports have suggested that a blockade or lack of N-type Ca 2ϩ channels can suppress the neuronal pathological processes of pain and ischemic brain injury in animal models. [4][5][6] Therefore, drugs with an N-type Ca 2ϩ channel-blocking property would become beneficial for patients with such neuronal diseases. 7,8) Cilnidipine is a Ca 2ϩ channel blocker with suppressive effects on L-and N-type Ca 2ϩ channels, 9,10) and is currently used for the treatment of essential hypertension in Japan.…”
Section: )mentioning
confidence: 99%
“…The mode of action of SNX 239, dexmedetomidine and morphine in blocking tactile allodynia is likely to be via inhibition of spinal neurotransmitter release. SNX 239 blocks a substantial fraction of glutamate release (Graham & Burgoyne, 1995;Takizawa et al, 1995), while the a 2 receptor has prominent presynaptic inhibitory e ects on release of both glutamate and substance P (Go & Yaksh, 1987;Anwyl, 1991). Morphine has both presynaptic e ects on neurotransmitter release and depresses excitability of postsynaptic neurones (Yaksh, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The ANP is a regulating hormone, which inhibits the release of renin, aldosterone, VAS and catecholamines [15]. Nitric Oxide (NO) inhibits the release of ANP [16]. The exact mechanism of ankle oedema by CCBs is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%